A NEW AUTHORITARIANISM. CORRELATIONS IN THE POLITICAL THEORY OBSERVABLE IN THE GOVERNMENT IN NICARAGUA - Vargas Machado, Camilo Andrés (2023)
This paper is the final product of investigation that seeks to found the discussion on the transformation of democracy to emerging authoritarianism in Latin-American. In which the contributions of three specific authors were correlated: J, Linz; C, Lesgart and O’Donnell, who offer their own concepts on the typologies of determined political governance, as can be seen in the representation of the case of the Republic of Nicaragua, and the actions undertaken by its main political actors. In this sense, it emerged from the use of analysis and descriptive methods typical of political science, that there are new authoritarianisms in the Latin American States, which will not dissipate, since, according of evidence, on contrary; these will be consolidated. Well, authoritarian regimes have eroded the democratic bases of the initial political system, which served them as means to gain access to political power, as can be seen in the case study, since initially it was based on the mechanisms of citizen participation, to later deviate from the proportions of a democracy, giving rise to personalistic, arbitrary and radical positions that redefine the ruler as a leader with an authoritarian inclination, where public liberties, right to dissent and to express political positions are limited.